Religious life for our world : creating communities of hope - Cimperman, Maria (Paulines Publications Africa; Nairobi, 2021)
"A valuable theological and pastoral resource for the conversion, transformation and revitalization needed in consecrated life today"--
Includes bibliographical references and index.
Keywords: Catholic Church -- Clergy -- Religious life; Monastic and religious life